Síntese e atividade antitumoral e antioxidante de calcogeno-amino timidinas (CAT) - Rosa, Raquel Mello da (2016)
This work aims the synthesis of new 5'-arilchalcogenil-3-animo-thymidine (5a-m) derivative containing chalcogenium or thymidines nucleosides derivatives (3-azidothymidine 1) with potential antioxidant and antitumor evaluation. The development of a synthetic route involving two transformations in a single reaction step was planned. The compounds exhibit changes at specific positions consisting in adding organochalcogenium at position 5 of 3-azidothymidine 1. The cleavage reaction of the corresponding aryl dichalcogenetes (4a-j) in THF followed by the addition of the reducing agent NaBH4 and EtOH, leading to the formation of nucleophilic species to react chalcogen through a bimolecular nucleophilic substitution reaction, these nucleophiles reacted with 3-azidothymidine mesilada 3 and along this same protocol, the reduction of the azide grouping of 3-azidothymidine mesilada 3 to their desired amines was performed forming the 5'-arilchalcogenil-3-animo-thymidine (5a-m) in yields in the range 20 -82%. The studies of reaction time and the amount of reducing agent were performed in order to optimize for the two desired reaction steps, which allowed quick access to a range of novel compounds. With properly characterized compounds, they have undergone as its antioxidant and anti-tumor potential